2005
DOI: 10.1038/sj.ijir.3901353
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction after pelvic surgery

Abstract: Pelvic surgeries are among the most common causes of organic sexual dysfunction in men and women. The impact of nerve-sparing surgery on potency has been well documented in radical prostatectomy. However, its impact on potency needs to be evaluated in other pelvic surgeries. Sexual dysfunction is highly prevalent even after multiple technical advances in the field of oncological surgeries. The prevalence varies from 8 to 82%, depending on the type of pelvic surgery. In females, sexual dysfunction has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
103
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 121 publications
2
103
1
3
Order By: Relevance
“…[1][2][3]9 Despite recent improvements in performing RP that have led to a considerable decrease in the treatmentassociated sequelae, ED still represents a major problem. 4 The main postulated cause of ED in these patients is the temporary cavernous nerve damage, resulting in penile hypoxia, smooth muscle apoptosis, fibrosis and veno-occlusive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3]9 Despite recent improvements in performing RP that have led to a considerable decrease in the treatmentassociated sequelae, ED still represents a major problem. 4 The main postulated cause of ED in these patients is the temporary cavernous nerve damage, resulting in penile hypoxia, smooth muscle apoptosis, fibrosis and veno-occlusive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…23 Reviews of the literatures have shown that age, obesity and urinary tract symptoms are the mostimportant factors attributed to the occurrence of ED. 1,5,[8][9][10]12,23 The appropriate dose of PGE1 used for ED treatment depends on the etiology. For instance, men with peripheral vascular causes for ED require higher IC dosing than men with neurogenic causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since penile rehabilitation is now being advocated by centers when erectile dysfunction is noted clinically after radical prostatectomy, 5 it would seem prudent to identify men who are having sex-related incontinence, since the embarrassment it causes might thwart the positive effects that are being attempted with penile rehabilitation. It seemed important to identify this variation of postoperative incontinence, and to attempt to obtain an initial estimate of its prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunction after pelvic surgery has been described in detail elsewhere. 5 Seddon classification of nerve injury includes 3 degrees of injury: neuropraxia, axonotmesis, and neurotmesis. Neuropraxia is the mildest form of nerve injury, which occurs from transient demyelination, and healing takes place over weeks to months.…”
mentioning
confidence: 99%